Determination of the Environmental Quality of the former Azalia and Chonta tailings dams (Pasco, Peru), through bird monitoring - Saenz Cortez, Carlos Alberto (2023)
Bird monitoring conducted in the former Azalia and Chonta tailings dams, located in the District of Goyllarisquizga (Pasco), conducted from March 9 to 12, 2021, has helped determining that the environmental quality is average. Furthermore, it has been pointed out that it is important to restore and reforest ecological components of the former Chonta and Azalia tailings dams, since according to the results obtained, 89.06% of the species found are registered on the IUCN Red List of threatened species, classified as Least Concern according to version 3.1 of the second edition of the IUCN Red List Categories and Criteria. Likewise, 10.92% of birds are endemic to the area, which means that they can only inhabit that type of ecosystem, and 3.36% of birds are cataloged as CITES and are listed in Appendix II of CITES, so it can be concluded that 89.06% of species are sensitive.